2002
DOI: 10.1104/pp.001602
|View full text |Cite
|
Sign up to set email alerts
|

The Branched-Chain Amino Acid Transaminase Gene Family in Arabidopsis Encodes Plastid and Mitochondrial Proteins

Abstract: Branched-chain amino acid transaminases (BCATs) play a crucial role in the metabolism of leucine, isoleucine, and valine. They catalyze the last step of the synthesis and/or the initial step of the degradation of this class of amino acids. In Arabidopsis, seven putative BCAT genes are identified by their similarity to their counterparts from other organisms. We have now cloned the respective cDNA sequences of six of these genes. The deduced amino acid sequences show between 47.5% and 84.1% identity to each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
139
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 33 publications
6
139
1
Order By: Relevance
“…AtBCAT2, -3, and -5 localize to chloroplasts, suggesting roles in BCAA synthesis (Diebold et al, 2002). AtBCAT4 is cytosolic (Schuster et al, 2006), and the location of AtBCAT6 is suggested to be cytosolic because of its lack of a defined target peptide sequence (Diebold et al, 2002). Complementation analysis in BCAT-deficient yeast strains confirmed the functions of AtBCAT1, -2, -3, -5, and -6 but not AtBCAT4 (Diebold et al, 2002).…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…AtBCAT2, -3, and -5 localize to chloroplasts, suggesting roles in BCAA synthesis (Diebold et al, 2002). AtBCAT4 is cytosolic (Schuster et al, 2006), and the location of AtBCAT6 is suggested to be cytosolic because of its lack of a defined target peptide sequence (Diebold et al, 2002). Complementation analysis in BCAT-deficient yeast strains confirmed the functions of AtBCAT1, -2, -3, -5, and -6 but not AtBCAT4 (Diebold et al, 2002).…”
mentioning
confidence: 73%
“…AtBCAT4 is cytosolic (Schuster et al, 2006), and the location of AtBCAT6 is suggested to be cytosolic because of its lack of a defined target peptide sequence (Diebold et al, 2002). Complementation analysis in BCAT-deficient yeast strains confirmed the functions of AtBCAT1, -2, -3, -5, and -6 but not AtBCAT4 (Diebold et al, 2002). AtBCAT1 is the most likely candidate for initiating BCAA breakdown (Schuster and Binder, 2005), although AtBCAT5 has also been found in mitochondrial fractions (Binder et al, 2007).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…mpg.de/general/ora/ora.shtml) of this clique revealed significant enrichment of nine enzymes belonging to amino acid metabolism, mainly amino acid degradation. This clique includes genes encoding catabolic enzymes of the Asp-family pathway, namely, Lys-Ketoglutarate Reductase/Saccharopine Dehydrogenase (Lys catabolism) 4,9 , Branched-chain amino acid Aminotransferase (likely functioning in Ile catabolism) 4,10 and Thr Aldolase (converting Thr into Gly). 11 In addition, this clique includes genes encoding five TFs that possess specific TFs domains, but their functions have not yet been characterized.…”
Section: A Friend In Need Is a Friend Indeedmentioning
confidence: 99%